Kiat Memotivasi Karyawan - Bambang Suseno Hastono (Efisiensi : Kajian Ilmu Administrasi, 2011)
Employee's motivation has become crucial for the organization to be enhanced because of the rapid changing situation faced by organization. High motivation to work will result in good behavior and job performance. Understanding some motivation theories and applying them properly will help a manager to find out the right methods to motivate the employees well. In addition to the changing employees paradigm, a manager should have good understanding about some factors that affect employee's motivation such as a good reward system and appraisal, physical and non-physical improvements and organizational culture. All of them are needeed to be implemented in order to motivate employees effectively.